Urban Life as Risk Factor for Aspergillosis - Grehn, Claudia; Eschenhagen, Patience; Temming, Svenja; Düesberg, Uta; Neumann, Konrad; Schwarz, Carsten (Frontiers in Cellular and Infection Microbiology, 2020)
Aspergillus fumigatus (Af) frequently colonizes the airways of patients with cystic fibrosis (CF) and can cause severe diseases, such as allergic bronchopulmonary aspergillosis, Af bronchitis or even Af pneumonia. However, risk factors, including environmental factors, for acquiring Af in the respiratory tract of patients with CF are rarely studied and described. The aim of this study was to investigate whether urban or rural life could affect colonization with Af in the respiratory tract of patients with CF. Due to privacy policy, registry data are usually not linked to patients´ home addresses. It is therefore very difficult to analyze the influence of the patient´s residential environment. This prospective questionnaire survey was carried out in 31 German CF centers in 2018. Only completed surveys, including a clearly assigned type of residential area were included. Statistical analysis was performed by chi-squared test and logistic regression models. A total of 1016 questionnaires were analyzed (Patients` age: 23±13; 0-88 years; female gender: n=492; 48%). The majority of patients with CF live in large cities (n =314; 30.9%) or urban districts (n=461; 45.4%). Prevalence of 30.2% was found for Af, within the 12 months of investigation period. Af colonization was significantly associated with urban life (p=0.004). Urban live should be considered as possible new risk factor for colonization with Af in the respiratory tract of patients with CF. These new results may raise the awareness of the influence of environmental factors on patient outcomes and should be included in patient guidance and preventive measures.